Intra-Annual Sea Level Fluctuations and Variability of Mesoscale Processes in the Northern Japan/East Sea From Satellite Altimetry Data - Trusenkova, Olga; Kaplunenko, Dmitry (Frontiers in Marine Science, 2022)
Intra-annual sea level fluctuations and variability of mesoscale processes based on eddy kinetic energy (EKE) were studied in the northern (northward of 41 N) Japan/East Sea (JES) using data from satellite altimetry for 1993–2020. Decomposition to empirical orthogonal functions (EOF) was performed of the high-pass filtered, with the cut-off period of 250 days, sea level anomalies. The leading mode accounting for the major fraction of the variance yielded sea level fluctuations which were simultaneous in the entire sea and occurred in the range from 70 to 250 days without any preferable timescale. EKE in the northern sea was also expanded to EOF and yielded the leading mode capturing mesoscale variability within the Primorye (Liman) Current and the Tsushima Warm Current. The seasonal signal was found in the simultaneous intra-annual sea level fluctuations, which matches that of EKE, and, as found in the earlier studies, of the mean currents. The sea level rises, the mean currents intensify and EKE increases in summer and fall and the opposite changes occur in winter and spring, with the seasonal extremes in October/November and March/April, respectively. This is in line with the EKE generation by instability of the mean currents. The intra-annual sea level fluctuations and EKE manifest rich variability on quasi-biennial, interannual and decadal timescales. However, in contrast with the seasonal signal, the low-frequency variability does not match, implying different kinds of forcing, probably by local wind in the northern JES and by the transport variations in the Korea – Tsushima Strait (KTS) in the southern JES. Intra-annual simultaneous SLA reveal changing relationship with Pacific Decadal Oscillation (PDO): both were in-phase in 1993–1994 and from late 2007 to 2013 and out-of-phase from 1997 to 2002, while there was no specific relationship in other times. However, the relationship of these SLA with the interannual KTS transport variation seems inconclusive.